2012
DOI: 10.1259/dmfr/22999207
|View full text |Cite
|
Sign up to set email alerts
|

Infraorbital ethmoid (Haller's) cells: a panoramic radiographic study

Abstract: Objective: Haller's cells or infraorbital ethmoid cells refer to the ethmoidal pneumatization of the superior aspect of the maxillary sinus and floor of the orbit. The clinical importance of these entities initiated this study with an aim to determine the prevalence and characteristics of Haller's cells on panoramic radiographs. Methods: The study group comprised 600 healthy adults of both genders with an age range of 18-60 years. One panoramic radiograph for each of the patients was made and interpreted for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
36
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 11 publications
12
36
2
Order By: Relevance
“…No statistically significant differences were noted in the occurrence of Haller's cells on the right and left side, which were 69 and 73 cells respectively. Similar findings were seen in study conducted by A Raina et al, [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No statistically significant differences were noted in the occurrence of Haller's cells on the right and left side, which were 69 and 73 cells respectively. Similar findings were seen in study conducted by A Raina et al, [9].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study analyses have been performed to determine the variations of Haller's cells with respect to gender, age, number, type and shape which were remotely been reported in the past. A study conducted by A Raina et al, [9] have reported the prevelance of hallers cells of 16% which lies in the same range as that of this study. Maximum number of cells between males and females which was consistent with the findings of N Basic et al, [10].…”
Section: Discussionsupporting
confidence: 87%
“…This result is similar with the study conducted by Riello and Boasquevisque, Zeinrich et al who found 10 % Haller cell in their study [20,21]. Raina et al noted 16 % of the study population possesses Haller cell [22]. Mamatha et al documented 17.5 % Haller cell in their study [16].…”
Section: Discussionsupporting
confidence: 90%
“…This result is contrary to former surveys [37], [38], [39]. As CBCT delivers detailed information on the ethmoid complex with lower costs compared to CT and the possibility of prompt information by implementation in an outpatient office [28], [29], we see further need for radiological investigation and clinical studies on Haller cells.…”
Section: Discussionmentioning
confidence: 61%